THE FORMULA OF AGATHA CHRISTIE’S DETECTIVE STORY THE THIRD-FLOOR FLAT - Yustin Sartika (LINGUA LITERA : journal of english linguistics and literature, 2022)
Abstract This research aims to explain the detective formula as portrayed in Agatha Christie’s The Third-Floor Flat short story and the techniques that are employed to maintain the suspense by using Cawelti’s formula theory. Cawelti explains there are four aspects of the classic detective’s formula: situation, the pattern of action, character and their relation, and setting. This research is descriptive qualitative research. The formulas of detective stories exist in The Third-Floor Flat. The plot goes straight on the definite formula: the preliminaries, birth of the plot, intentional misleading, the crime, grouping for the murderer by the police, friends, relatives, and amateur detective, failure of everybody, detective’s announcement of facts and proof. The author used some techniques such as the whodunit, metaphor, foreshadowing, and fake devices to maintain the suspense.